2004
DOI: 10.1007/s00421-004-1166-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computerized methods for detecting the ventilatory thresholds

Abstract: The aim of this study was to compare computerized automatic methods to detect the ventilatory threshold (VT). Thirty apparently healthy and physically active volunteers [22.5 (6.5) years; 1.72 (0.08) m; 71.9 (8.5) kg] were submitted to a progressive and maximal cycle exercise. The gas exchange was monitored breath-by-breath with a fast gas analyser. The VT and respiratory compensation (RC) were automatically detected based on the respiratory exchange ratio, the ventilatory equivalent for O2 and the ventilatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 33 publications
5
47
0
5
Order By: Relevance
“…Kelly 36 observed that the results obtained by the original mathematical method of Beaver et al 9 presented a major estimate standard error, when compared to MM RSS . Santos et al 35 found for this method, percentage indices of 83% of VO 2max . In our study, we observed high intensities of AT 31 by means of MM slope , indicating a possible method inaccuracy.…”
mentioning
confidence: 77%
“…Kelly 36 observed that the results obtained by the original mathematical method of Beaver et al 9 presented a major estimate standard error, when compared to MM RSS . Santos et al 35 found for this method, percentage indices of 83% of VO 2max . In our study, we observed high intensities of AT 31 by means of MM slope , indicating a possible method inaccuracy.…”
mentioning
confidence: 77%
“…The 3 most common definitions of the VT are the following: (1) the point at which a systematic increase in the ventilatory equivalent for oxygen (V E/V O 2 ) occurs without an increase in the ventilatory equivalent for carbon dioxide (V E/V CO 2 ), (2) the point at which a systematic rise in end-tidal oxygen pressure (P ET O 2 ) occurs without a decrease in the end-tidal carbon dioxide pressure (P ET CO 2 ), and (3) the departure of V CO 2 from a line of identity drawn through a plot of V CO 2 versus V O, often called the V-slope method. 18 When determined visually, these methods on average result in VT values at a similar percentage of V O 2max . 19 Although modern equipment that measures metabolic parameters usually quantifies this point automatically using one of several published or empirical algorithms, it should be validated visually by an experienced reviewer.…”
Section: Maximal Oxygen Uptakementioning
confidence: 92%
“…Verificamos uma correlação significativa entre os métodos Dmáx e R (r =0,62 p< 0,05). Resultados semelhantes foram encontrados em outros estudos, nos quais não existiam diferenças significativas entre a determinação de limiar anaeróbio por R e por outros métodos ventilatórios e lactacidêmicos 5,[14][15][16][17]23 . Estes resultados em conjunto demonstram que a determinação de limiar anaeróbio pela R pode ser utilizada como um parâmetro independente para a detecção do limiar anaeróbio.…”
Section: Resultsunclassified
“…Em razão deste acoplamento da respiração com o gesto técnico, torna-se praticamente impossível a detecção dos limiares ventilatórios nesta população 20,30 . Além disso, partindo do principio de que a mensuração do lactato é uma técnica invasiva e de alto custo financeiro, alguns autores sugerem a utilização da R como um método alternativo não-invasivo, reproduzível, de fácil aplicação e com menor custo de manutenção da técnica para a detecção do limiar anaeróbio 5,7,13,15,17,[21][22][23] . A proposta destes autores é que o limiar anaeróbio seja identificado pela R a partir do ponto de aumento desproporcional ou excedente de um valor pré-determinado.…”
Section: Conclusãounclassified
See 1 more Smart Citation